Was Mesosaurus a Fully Aquatic Reptile? - Nuñez Demarco, Pablo; Meneghel, Melitta; Laurin, Michel; Piñeiro, Graciela (Frontiers in Ecology and Evolution, 2018)
Mesosaurs have been considered strictly aquatic animals. Their adaptations to the aquatic environment are well known and include putative viviparity as the reproductive strategy along to the presence of several skeletal characters such as a long, laterally compressed tail, long limbs, particularly the foot larger than the manus, pachyostotic bones, mainly in the ribs, and osteosclerosis in the humerus. They also possessed non-coosified girdle bones and incompletely ossified epiphyses, although there could be an early fusion of the front girdle bones to form the scapulocoracoid in some specimens. Some of these features, however, are shared by most of the basal tetrapods which are considered as semiaquatic and even terrestrial. The study of vertebral column and limbs provides essential clues about the locomotor system and the lifestyle of early amniotes. In this study, we have found that the variation of the vertebral centrum length along the axial skeleton of Mesosaurus tenuidens fits better with a semi-aquatic morphometric pattern, as shown by comparisons with other extinct and extant taxa. Whereas well-preserved mesosaur skeletons are mostly represented by juveniles and young adults that inhabited aquatic environments, more mature individuals might hypothetically have spent time on land. This is tentatively pointed out by taphonomic factors such as the scarce representation and poor preservation of remains of mature individuals in the fossiliferous levels, and also by anatomy of the appendicular bones, and particularly the strongly ossified epiphyses and tarsus.